Analysing China's Population
IX, 270 p. 47 illus.
Keywords: Based on China’s recently released 2010 population census data, this edited volume analyses the most recent demographic trends in China, in the context of significant social and economic upheavals. The editor and the expert contributors describe the main features of China’s demography, and focus on the details of this latest phase of its demographic transition. The book explores such striking characteristics of China’s demography as the changing age and sex population structure; recent trends in marriage and divorce; fertility trends with a focus on sex imbalance at birth; the demography of the ethnic minorities and recent mortality trends by sex. Analysing China's Population: Social Change in a New Demographic Era examines and assesses the impact of changes that in the coming decades will be crucial for individuals, and the larger society and economy of the nation.